FCGR1A Serves as a Novel Biomarker and Correlates With Immune Infiltration in Four Cancer Types - Xu, Ji-li; Guo, Yong (Frontiers in Molecular Biosciences, 2020)
Background FCGR1A encodes a protein that plays an important role in the immune response. The prognostic impact and immune infiltration of FCGR1A in heterogeneous cancers remain unclear. Methods Differential expression of FCGR1A between tumor and normal tissues and the discrepancies in overall survival (OS) among diverse cancer types were performed by Gene Expression Profiling Interactive Analysis. The correlation between FCGR1A and immune cells or gene marker sets of immune infiltrates was analyzed via Tumor Immune Estimation Resource (TIMER). Gene Ontology (GO), Kyoto Encyclopedia of Genes and Genomes (KEGG) analysis, and protein-to-protein interaction (PPI) network were used to explore the function and related genes of FCGR1A. The relationships among these genes were further analyzed by TIMER. Results FCGR1A is highly expressed in various cancer types. FCGR1A was significantly correlated with the OS of cervical and endocervical cancer (CESC), cholangiocarcinoma (CHOL), kidney renal clear cell carcinoma (KIRC), and skin cutaneous melanoma (SKCM) (P < 0.05). High expression of FCGR1A meant a better prognosis besides KIRC. FCGR1A showed significant differences at different stages of KIRC and SKCM (P < 0.05). Furthermore, FCGR1A was notably associated with infiltrating levels of CD4+ T cells, CD8+ T cells, B cells, macrophages, neutrophils, and dendritic cells in the four cancers (P < 0.05). FCGR1A also showed close relevance with different immune gene markers. The copy number variation of FCGR1A significantly influenced the abundance of immune infiltration in KIRC and SKCM. GO, KEGG analysis, and PPI network analysis revealed that FCGR1A is involved in many pathophysiological processes and was most related to FCGR3A. And this gene indicated highly significant positive correlations with FCGR1A in four cancers. Conclusion FCGR1A may be a potential prognostic biomarker and related to immune infiltration levels in diverse cancers, especially in CESC, CHOL, KIRC, and SKCM. Besides, FCGR1A may be involved in the activation, regulation, or induction of immune cells and diverse physiological and pathological processes.